2014
DOI: 10.1371/journal.pone.0089707
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nephritogenic Serum Galactose-Deficient IgA1 in IgA Nephropathy following Tonsillectomy and Steroid Therapy

Abstract: BackgroundRecent studies have shown that galactose-deficient IgA1 (GdIgA1) has an important role in the pathogenesis of IgA nephropathy (IgAN). Although emerging data suggest that serum GdIgA1 can be a useful non-invasive IgAN biomarker, the localization of nephritogenic GdIgA1-producing B cells remains unclear. Recent clinical and experimental studies indicate that immune activation tonsillar toll-like receptor (TLR) 9 may be involved in the pathogenesis of IgAN. Here we assessed the possibility of GdIgA1 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 54 publications
2
49
0
Order By: Relevance
“…27 Indeed, we recently showed that Gd-IgA1 was significantly decreased after tonsillectomy in patients with IgAN, who also showed a significant improvement in urinalysis just after tonsillectomy. 26 This study further showed that patients with IgAN with abundant expression of Stalk-1 in tonsillar GC showed more proteinuria and better clinical outcomes after the tonsillectomy, including improvement of proteinuria and decrease of serum Gd-IgA1 levels. These findings suggest that palatine tonsils with overexpression of APRIL may be one of the major delivery source of nephritogenic IgA.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…27 Indeed, we recently showed that Gd-IgA1 was significantly decreased after tonsillectomy in patients with IgAN, who also showed a significant improvement in urinalysis just after tonsillectomy. 26 This study further showed that patients with IgAN with abundant expression of Stalk-1 in tonsillar GC showed more proteinuria and better clinical outcomes after the tonsillectomy, including improvement of proteinuria and decrease of serum Gd-IgA1 levels. These findings suggest that palatine tonsils with overexpression of APRIL may be one of the major delivery source of nephritogenic IgA.…”
Section: Discussionmentioning
confidence: 52%
“…However, some patients notably showed improved hematuria and serum Gd-IgA1 levels after steroid pulse therapy after the tonsillectomy compared with just after tonsillectomy, suggesting that Gd-IgA1-producing cells may also be localized outside the tonsils. 26 Recent data have revealed that some of the NALT-derived and -activated B cells and even tonsillar B cells can migrate from inductive mucosal sites to systemic effector sites, including bone marrow, through guiding adhesion molecules and chemokine/chemokine receptors. 52,53 In addition, our recent study revealed that IgA1 secreted by Epstein-Barr virusimmortalized B cells from the peripheral blood of patients with IgAN was mostly polymeric with Gd sialylated O-glycans.…”
Section: Discussionmentioning
confidence: 99%
“…Nakata et al found that serum GdIgA1 levels decreased by 59% after tonsillectomy, thus indicating that the palatine tonsils are probably a major sites of GdIgA1-producing cells. 23 In fact, Japanese Society of Nephrology clinical guidelines for IgAN suggested tonsillectomy plus steroid pulse therapy to achieve early CR in 2011. 24 Tonsillectomy may delay the progression of IgAN especially in patients with macrohematuria.…”
mentioning
confidence: 99%
“…18 Observations have suggested that tonsillectomy could reduce the incidence of microhematuria and proteinuria in patients with normal renal function and mild proteinuria, 19,20 as well as the level of aberrantly galactosylated IgA1 in patients with IgAN. 21,22 However, the definitive pathogenic mechanism of tonsillitis in IgAN is still debated. We hypothesized that the overactive state of the tonsils and tonsillitis-mediated inhibition of immune tolerance might facilitate IgAN.…”
Section: Discussionmentioning
confidence: 99%